THE LOCALITY OF TAFSÎR AL-AZHÂR HAMKA: An Analitical Study of Surah Âli ‘Imrân Interpretation - Badruzaman, Abad; Aziz, Thoriqul (ULUL ALBAB Jurnal Studi Islam, 2020)
Recently, many tafsîr (interpretive) studies in Indonesia have been directed to the works of "children of the nation" in the local-regional level and Indonesian-language tafsîr. Most of Archipelago-nuanced tafsîr nowadays are used as research objects, from thesis level to dissertation. This article will use Tafsîr al-Azhâr Hamka as the object by emphasizing on the locality aspect by using surah Ali ‘Imrân as the sample. Locality can be included in the Adabî-Ijtima‘î style (social). Therefore, as a foundation methodology, the style will be firstly discussed in general. This study uses analytical descriptive by citing Karl Mannheim’s theory of Sociology. The result is that locality is found in Tafsir al-Azhâr in surah Ali ‘Imrân i.e. locality in language and socio-culture. This locality shows that Hamka is a mufasir (interpreter) who always contextualizes important themes inside a verse so that the meaning and message of the verse are easily understood and applied in the real community where Hamka lives in.